Analysis of Some Recently Proposed Modifications to the Eddy Dissipation Concept (EDC). Issue 6 (2nd June 2020) - Ertesvåg, Ivar S.
ABSTRACT: The widespread use of the Eddy Dissipation Concept (EDC) of Magnussen has led to a number of suggestions to modify the model. These modifications are to a varying extent in agreement with the underlying ideas of EDC. This article analyzes 20 such attempts. The original formulations of EDC are reviewed and explained. Often, users tend to neglect the expressions for the fraction of reacting fine structures. This part of the model includes some Reynolds number dependency, which is acting where such effects have been requested. The possibly unintended, but widely used, EDC modification in the Ansys Fluent implementation is discussed and analyzed. It is shown that some of the claimed defects of EDC are caused by this implementation. A total of 12 articles proposing changes of the EDC constants are reviewed and the suggestions analyzed and discussed with respect to the reaction rate, fine-structure model and viscous effects. Models combining Arrhenius and EDC at low turbulence Reynolds numbers and a model based on fractal theory are commented.